Toward Directing Opioid Receptor Signaling to Refine Opioid Therapeutics - Grim, Travis W. (Biol Psychiatry, 2019)
The mu opioid receptor (MOR) is a diversely regulated target for the alleviation of pain in the clinical setting. However, untoward side effects such as tolerance, dependence, respiratory suppression, constipation, and abuse liability detract from their usefulness. Studies in genetically modified rodent models suggest that activating G protein signaling pathways while avoiding phosphorylation of the receptor or recruitment of βarrestin scaffolding proteins could preserve the analgesic properties of MOR agonists while avoiding certain side effects. With the development of novel MOR “biased” agonists, which lead to preferential activation of G protein pathways over receptor phosphorylation, internalization or interaction with other effectors, this hypothesis can be tested in a native, physiological setting. Overall, it is clear that the MOR is not a simple on and off switch and that the diverse means by which the receptor can be regulated may present an opportunity to refine therapeutics for the treatment of pain.